2013
DOI: 10.2474/trol.8.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transfer Layer on Ultra Low Friction of CNx Coating under Blowing Dry Ar

Abstract: In order to clarify the ultra low friction mechanism of Carbon Nitride (CN x ) coatings under blowing dry Ar, thickness and area of transfer layers on mating surface were in-situ observed with an optical microscope during sliding against a sapphire hemisphere under blowing dry Ar. During sliding, thickness of transfer layer from CN x coating to a sapphire hemisphere increased and leaded to ultra low friction. When thickness and area of transfer layer was thick and small respectively, ultra low friction was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…On the other hand, although the formation of a uniform tribofilm on the wear scar of the ball surface is beneficial for obtaining super-low friction of CNx coatings in N 2 gas environment, the tribofilm is unstable, and it has been found that a random lost or detachment of tribofilm on the ball surface occasionally leading to high and unstable friction coefficients (μ > 0.3). 12 On the contrary, high and unstable friction coefficients were not observed in the current work when the contact material combination of self-mated CNx coatings was generated. Therefore, the stable and low friction behaviour of CNx/CNx in N 2 gas stream can be attributed to the formation of self-mated CNx coatings.…”
Section: Effects Of Number Of Cycles and Gas Atmospheres For Pre-slidingcontrasting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, although the formation of a uniform tribofilm on the wear scar of the ball surface is beneficial for obtaining super-low friction of CNx coatings in N 2 gas environment, the tribofilm is unstable, and it has been found that a random lost or detachment of tribofilm on the ball surface occasionally leading to high and unstable friction coefficients (μ > 0.3). 12 On the contrary, high and unstable friction coefficients were not observed in the current work when the contact material combination of self-mated CNx coatings was generated. Therefore, the stable and low friction behaviour of CNx/CNx in N 2 gas stream can be attributed to the formation of self-mated CNx coatings.…”
Section: Effects Of Number Of Cycles and Gas Atmospheres For Pre-slidingcontrasting
confidence: 61%
“…Two‐step friction test is proved to be an effective technique for obtaining the contact material combination of self‐mated CNx coatings, and it provides a new pathway for studying the potential outstanding tribological properties of self‐mated CNx coatings in N 2 gas environment. On the other hand, although the formation of a uniform tribofilm on the wear scar of the ball surface is beneficial for obtaining super‐low friction of CNx coatings in N 2 gas environment, the tribofilm is unstable, and it has been found that a random lost or detachment of tribofilm on the ball surface occasionally leading to high and unstable friction coefficients (μ > 0.3) . On the contrary, high and unstable friction coefficients were not observed in the current work when the contact material combination of self‐mated CNx coatings was generated.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the transfer layers are generated through running-in, resulting in a decrease in friction. 34,37,40 Although an optical microscope is able to detect transfer layers, spectroscopic analysis (e.g. Raman spectroscopy, X-ray photoelectron spectroscopy, and reflectance spectroscopy) is required to analyze DLC structures.…”
Section: Effect Of DC Discharge On the Friction Of The Si-dlc Coatingmentioning
confidence: 99%
“…Nitride doping is one well-known method to realize super-low friction and adhesion. [38][39][40][41] Transfer layers derived from carbon nitride (CNx) coatings show a high sp 2 fraction due to restructuring of the carbonaceous structure by the desorption process of nitrogen atoms. 40,42 The transfer layers with a high sp 2 fraction provide lower friction due to the lower shear strength of the graphite-like structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation